The impact of myo-inositol on glycoregulation and lipid profile - Stanković, Veroslava; Jović, Dragana; Mitić, Simonida; Mitić, Sava; Zuber, Andrijana (Education and Research in Health Sciences, 2025)
Myo-inositol has attracted attention due to its potential as a therapeutic agent in the treatment of metabolic disorders, particularly diabetes mellitus (DM) and lipid profile disorders. This study investigates the role of myo-inositol in the regulation of glucose metabolism, insulin sensitivity, and lipid profile, with a special focus on its impact on type 2 diabetes and associated lipid disorders. Myo-inositol plays a key role in insulin signaling by regulating insulin action in target tissues, enhancing glucose uptake, and reducing insulin resistance. Clinical studies show that myo-inositol supplementation can lead to significant improvements in glycemic control, including reduced fasting glucose levels and HbA1c, and affects the lipid profile by lowering total cholesterol, LDL, and triglycerides, while increasing HDL levels. Furthermore, myo-inositol shows potential in addressing diabetes-related complications, including diabetic nephropathy and oxidative stress. These findings suggest potential of myo-inositol as an adjunctive therapy in the treatment of diabetes and lipid disorders. However, further clinical research with larger sample sizes is needed to fully understand the long-term effects and safety in patients with diabetes. This review highlights the need for further studies to optimize the therapeutic applications of myo-inositol in metabolic disorders.
Keywords: myo-inositol; insulin sensitivity; lipid profile; glycoregulation